Identifying misleading corporate narratives: The application of linguistic and qualitative methods to commercial determinants of health research. - Iona Fitzpatrick; Adam Bertscher; Anna B Gilmore (Public Library of Science (PLoS), 2022)
Narratives are key to the way corporations represent themselves to the outside world, are important to the development of shared understandings and ultimately determine whether and how corporations are able to influence societal norms and participate in policy debates. A leaked corporate affairs strategy document, from the world's largest transnational tobacco company, Philip Morris International (PMI), suggests a company concerned about credibility; it highlights "normalization" as a key strategic priority until at least 2024. This suggests that the PMI are seeking to rehabilitate their image and alter perceptions of their business. We designed a mixed-methods analysis of corporately authored content, combining quantitative querying of large bodies of text (Corpus Linguistics) with inductive coding of key themes to critically examine PMI's corporate language and how these themes might impact public health debates. We systematically analysed a sample of PMI's corporate communications (n = 170), comparing investor-facing (investor reports, slides and presentations as well as annual reports) and public-facing (YouTube content and Webpage content) communications covering a period of eight years (2012-2019). Our analysis identifies how PMI's misleading external communication contradicts its core business focus and may threaten public health. In public-facing communications, PMI stress their commitment to transformation and change, while in investor-facing communications, they focus on cigarettes and reiterate the strength of their existing cigarette brand portfolios. This suggests that webpage and YouTube content provide a means through which PMI attempt to neutralise negative public perception of tobacco-product related harms and to present themselves as advocates of "better" consumer choice and even public health. The recurrence of transformation, sustainability, and science, as well as the co-option of united-nations terminology in their external-facing communications may serve to legitimise their involvement in policy arenas from which they currently excluded. We present a novel method through which corporate narratives can be monitored and critically assessed.